Role of public health professionals in the climate and ecological crisis: a qualitative study - Anya Göpfert; Maria Van Hove; Peter Davey (BMJ Open)
Background The climate and ecological emergency is the single biggest health threat facing humanity, yet it is not clear to what extent the public health workforce have been involved in work on this topic. This research aimed to establish what public health consultants working in local authorities in England perceive their role to be, whether the climate crisis is seen as a core component of public health and to identify barriers to action.Methods Semi-structured interviews were undertaken with a purposive sample (n=11) of local authority public health consultants in England. Participants were recruited via public health organisations, social media or snowballing. Thematic content analysis was used to identify codes and themes.Results Public health professionals have started work on climate change but reported being unclear about their role and feeling isolated working on this topic. Barriers to action included shortage of financial resources, communication tools and capacity, limited sharing of best practice, lack of local expertise and conflict between the need for action on climate change and other urgent issues.Conclusion We highlight the need to urgently address existing barriers to enable this important part of the public health workforce to play their role in tackling the climate and ecological crisis.